2015
DOI: 10.1530/erc-15-0123
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular endothelial growth factor in prostate cancer

Abstract: Prostate cancer (PCa) is the most common malignancy affecting men in the western world. Although radical prostatectomy and radiation therapy can successfully treat PCa in the majority of patients, up to w30% will experience local recurrence or metastatic disease. Prostate carcinogenesis and progression is typically an androgen-dependent process. For this reason, therapies for recurrent PCa target androgen biosynthesis and androgen receptor function. Such androgen deprivation therapies (ADT) are effective initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 159 publications
(156 reference statements)
1
40
0
Order By: Relevance
“…Pro-angiogenic pathway mechanisms stimulate tumor growth in many types of cancers, so therapies which target in tumor vasculature, as well as VEGF, PDGF, and FGF receptors, have been noticed (de Brot et al, 2015;Zhao and Adjei, 2015). Our research group has already shown the anti-PCa effects of Nintedanib in vitro, against both androgen dependent and androgen-independent human PCa cell lines (Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Pro-angiogenic pathway mechanisms stimulate tumor growth in many types of cancers, so therapies which target in tumor vasculature, as well as VEGF, PDGF, and FGF receptors, have been noticed (de Brot et al, 2015;Zhao and Adjei, 2015). Our research group has already shown the anti-PCa effects of Nintedanib in vitro, against both androgen dependent and androgen-independent human PCa cell lines (Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…VEGF regulation is complex and occurs at both transcriptional and post-transcriptional levels [21,22,23]. While the VEGF promoter lacks a TATA-binding site, it contains a GC-rich core promoter region and additional distal enhancer sites including hypoxia response elements that bind HIF1-α [24] (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant differently expressed lncRNA was LINC00087, which competitively regulated vascular endothelial growth factor (VEGF) and cyclin D2 (CCND2). Overexpression of the differential gene VEGF could promote angiogenesis and tumourogenesis in prostate cancer, and targeting the VEGF receptor pathway had shown promising early clinical application [30, 31]. Although CCND2 was a non-differential gene, LINC00087 which competitively regulated it were differentially expressed.…”
Section: Resultsmentioning
confidence: 99%